2015
DOI: 10.1111/acel.12422
|View full text |Cite
|
Sign up to set email alerts
|

Specific protein homeostatic functions of small heat‐shock proteins increase lifespan

Abstract: SummaryDuring aging, oxidized, misfolded, and aggregated proteins accumulate in cells, while the capacity to deal with protein damage declines severely. To cope with the toxicity of damaged proteins, cells rely on protein quality control networks, in particular proteins belonging to the family of heat‐shock proteins (HSPs). As safeguards of the cellular proteome, HSPs assist in protein folding and prevent accumulation of damaged, misfolded proteins. Here, we compared the capacity of all Drosophila melanogaster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 70 publications
3
45
0
2
Order By: Relevance
“…Mild temperature hardening in nature can increase insects’ thermotolerance 51 ; thus, the time at which insect samples are collected from the field also influences adult longevity under heat stress. Some previous studies also reported that heat stress increased the longevity of some Drosophila species 62 , such as D . melanogaster males (exposure of adults to 34 °C for 3 h) 63 , parasitoids, such as females of the wasp A .…”
Section: Discussionmentioning
confidence: 68%
“…Mild temperature hardening in nature can increase insects’ thermotolerance 51 ; thus, the time at which insect samples are collected from the field also influences adult longevity under heat stress. Some previous studies also reported that heat stress increased the longevity of some Drosophila species 62 , such as D . melanogaster males (exposure of adults to 34 °C for 3 h) 63 , parasitoids, such as females of the wasp A .…”
Section: Discussionmentioning
confidence: 68%
“…7a , Supplementary Figure 5, Supplementary Table 2 ). This overlap is particularly noteworthy for protein aggregation processes, as this family of small chaperones has been reported to mitigate polyglutamine toxicity and extend lifespan 17 , 18 , 36 . Five alpha-crystallin/sHSP genes were upregulated in E(z) mutants: Hsp23, Hsp26, Hsp27, CG13133 , and CG7409 .…”
Section: Resultsmentioning
confidence: 99%
“…We speculated that nutrition deficiency accelerated HSP70-mediated cell damage in ticks (Figure 10). The expression of HSP with antioxidant activity extends lifespan via regulating the downstream protein autophagy-related gene 7 (Morrow et al, 2004;Liao et al, 2008;Chen et al, 2012;Sarup et al, 2014;Vos et al, 2016), while HSP depletion reduces the number of viviparous offspring and simultaneously increases the number of premature nymphs, suggesting an unexpected role in aphid embryogenesis and eclosion (Will et al, 2017). Therefore, it is suggested that RH36 gene regulates vitellogenin uptake via HSP70 protein and extends lifespan of ovary to improve oviposition rate.…”
Section: Discussionmentioning
confidence: 99%